PENGARUH MODEL PEMBELAJARAN CHILDREN LEARNING IN SCIENCE (CLIS) TERHADAP PEMAHAMAN KONSEP IPA SISWA KELAS III SD NEGERI GUGUS I SANDUBAYA TAHUN AJARAN 2019/2020 - Muhammad Asrori Novani Wibawa; Ratnadi Ratnadi; Lalu Hamdian Affandi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2020)
This study aims to find out the influence of Children Learning in Science (CLIS) learning model on students’ understanding concept of natural science grade III SDN Cluster I Sandubaya in Academic Year 2019/2020. This study is an experimental study using a quasi-experimental design type nonequivalent control group design. The subject has chosen purposively from grade III SDN at Cluster I Sandubaya that is SDN 48 Cakranegara totaling 47 students. The data collected by observation and test. The data analyzed by an independent sample t-test. Based on the results of the statistically obtained value t-count of 4,547 > t-table of 2,014. Besides that, it is known that the average value of the post-test in the experimental class was 82,591, while the average value of the post-test control class was 70,142. Thus it can be concluded that there is influence of Children Learning in Science (CLIS) learning model on students’ understanding concept of natural science grade III SDN Cluster I Sandubaya in Academic Year 2019/2020.